The Impact of Genre-Based Instruction on Iranian Intermediate EFL Learners’ Writing Skills - Atefeh Mohseni (Vision: Journal for Language and Foreign Language Learning, 2021)
The teaching of writing skills includes different methods and approaches. English language learners should be equipped with genre-based pedagogy to be able to write for specific settings. However, the idea of using Genre-based instruction of writing in non-native English-speaking countries has empirically received inadequate attention. This study aimed to investigate the impact of GBI on writing skills. Genres are Argumentative, Discussion, Explanation, and Exposition. This study used a quasi-experimental design. Fifty-one male students majoring in aviation courses in civil aviation technology of Tehran with an intermediate level of proficiency were assigned to experimental and control groups. The author examined their proficiency by Michigan English language assessment Battery (MELAB test) and tested their writing skills by administering a writing test of TOEFL iBT 2008. The control group took part in the traditional teaching of writing, and the experimental group was taught explicitly through the GBI method based on a lesson plan proposal. Four pre-and post-tests were taken by two groups to check the writing GBI progress. Independent sample t-tests revealed that the writing GBI could significantly improve the coherence, cohesion, and organization of writing. This study can benefit EFL practitioners by shedding light on how we can implement GBI of writing in an authentic classroom situation.